Inovasi Produk Akad Rahn dalam Pengembangan Gadai Emas Perbankan Syariah - Mahdania Mahdania; Harfiyan Syahputra; Muhammad Ulfa Chairi; Dimaz Alfian Frastianda; Husni kamal (Journal of Islamic Economics and Finance, 2025)
This study aims to examine the innovation of rahn contract products in the development of gold pawn services in Islamic banking in Indonesia. Akad rahn is a sharia-based short-term financing instrument that provides liquidity solutions for the community without involving elements of riba, gharar, and maisir. As the need for fast, secure, and sharia-compliant financial services increases, innovation in rahn products is of strategic urgency. This research uses a qualitative descriptive approach with a literature study of literature, reports of Islamic financial institutions, and related regulations. The results of the study show that rahn product innovation is carried out through three main aspects: (1) the development of the form of contract, such as the combination of rahn with ijarah or mudharabah; (2) the use of digital technologies such as e-KYC and AI to accelerate services; and (3) the expansion of socio-economic benefits, especially for MSMEs. The study also found that the increase in gold prices has also encouraged the increase in the use of gold pawns as an alternative financial solution. Therefore, Islamic banking needs to continue to develop gold pawn services based on rahn contracts to remain competitive, inclusive, and sharia-compliant.